2022
DOI: 10.1021/acs.biomac.2c00202
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Arborescent Polypeptide-Based Unimolecular Micelles: Synthesis, Characterization, and Drug Encapsulation

Abstract: This paper reports novel hybrid arborescent polypeptides based on poly­(γ-benzyl l-glutamate)-co-poly­(γ-tert-butyl l-glutamate)-g-polysarcosine [P­(BG-co-Glu­(OtBu))-g-PSar]. The synthesis is launched by ring-opening polymerization (ROP) of N-carboxyanhydride of γ-benzyl l-glutamate (BG-NCA) and γ-tert-butyl l-glutamate (Glu­(OtBu)-NCA) to synthesize a random copolymer P­(BG-co-Glu­(OtBu)) serving as a precursor for the arborescent system, followed by deprotection of the tert-butyl (tBu) groups to afford free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…BLG-NCA affords poly­(γ-benzyl- l -glutamate) (PBLG) which is a helical polymer with biomimetic secondary structuring properties, while its deprotected form, polyglutamic acid (PGA), is water-soluble and pH-responsive . Polymers ,,, and copolymers , of PBLG or PGA derivatives have potential applications in bioactive substance delivery, and the preparation of antibacterial agents or biomaterials …”
Section: Resultsmentioning
confidence: 99%
“…BLG-NCA affords poly­(γ-benzyl- l -glutamate) (PBLG) which is a helical polymer with biomimetic secondary structuring properties, while its deprotected form, polyglutamic acid (PGA), is water-soluble and pH-responsive . Polymers ,,, and copolymers , of PBLG or PGA derivatives have potential applications in bioactive substance delivery, and the preparation of antibacterial agents or biomaterials …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the application of UIMs in tumor therapy has received increasing attention due to their excellent stability in the microenvironment of living organisms and unexpected effects through the enhanced permeability and retention effect of solid tumors. 25,26 A variety of studies have been conducted to show their excellent performance in drug delivery, 27 in vivo imaging, 28 chemotherapy, 29 photothermal therapy, 30 photodynamic therapy 31 and so on. Compared with traditional chemotherapy and radiotherapy, photothermal therapy (PTT) and photodynamic therapy (PDT) are two minimally invasive, highly effective optical therapies with few side effects, which have become a hot research spot in the field of tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their special structure, Zn‐CuO NPs suffer from low solubility. Polymeric micelles as a novel drug delivery system have the advantages of prolonging drug circulation time, enhancing drug accumulation, improving drug dissolution range, and reducing side effects 33 . In this study, we used surfactants and polyether polyol as stabilizers to prepare stabilized nanoparticles by strong ultrasound technique encapsulation to enhance the durability of metal nanoparticles, reduce their accumulation, enhance their distribution, and form a nanosystem of 50‐nm metal nanomicelles.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric micelles as a novel drug delivery system have the advantages of prolonging drug circulation time, enhancing drug accumulation, improving drug dissolution range, and reducing side effects. 33 In this study, we used surfactants and polyether polyol as stabilizers to prepare stabilized nanoparticles by strong ultrasound technique encapsulation to enhance the durability of metal nanoparticles, reduce their accumulation, enhance their distribution, and form a nanosystem of 50‐nm metal nanomicelles. We continued the characterization using transmission electron microscopy (TEM) and found that the metal nanoparticles were dispersed in the interior of the micellar system and the micellar encapsulation improved the homogeneity of the metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%